The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1973
DOI: 10.1159/000122160
|View full text |Cite
|
Sign up to set email alerts
|

Further Evidence on the Intrahypothalamic Locus for Androgenization of Female Rats

Abstract: Female rats, 5 days of age, received micropellets of a testosterone-propionate (TP)-paraffm mixture in the brain or under the skin, pellets of paraffin alone in the brain, or no treatment. The only animals that developed the acyclic, anovulatory syndrome as adults were those that had TP implanted in the brain. The most effective site for producing the syndrome was the ventromedial-arcuate area of the hypothalamus. The shortest latencies to onset of the syndrome occurred in animals with TP at the anterior porti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1975
1975
1986
1986

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…progestin receptor induction and changes in various enzyme activities (see 58). Within the developing rodent brain, estrogen-concentrating hypothalamic sites are implicated in brain sexual differentiation by the efficacy of micro-implants of testosterone propionate and estradiol in this region (17,28,69,70) and by the demonstration that neurite outgrowth induced by estradiol in organ cultures of neonatal mouse hypothalamus emanates from estrophilic neu rons (92). However, because many neurons project outside their immediate brain region, it is conceivable and in fact likely that some steroid effects may be manifested at the synaptic endings of a nonestrophilic brain area even though the primary site of action is an estrophilic region (60).…”
Section: Concluding Remarks: Actions Of Gonadal Steroids On Neural Anmentioning
confidence: 99%
“…progestin receptor induction and changes in various enzyme activities (see 58). Within the developing rodent brain, estrogen-concentrating hypothalamic sites are implicated in brain sexual differentiation by the efficacy of micro-implants of testosterone propionate and estradiol in this region (17,28,69,70) and by the demonstration that neurite outgrowth induced by estradiol in organ cultures of neonatal mouse hypothalamus emanates from estrophilic neu rons (92). However, because many neurons project outside their immediate brain region, it is conceivable and in fact likely that some steroid effects may be manifested at the synaptic endings of a nonestrophilic brain area even though the primary site of action is an estrophilic region (60).…”
Section: Concluding Remarks: Actions Of Gonadal Steroids On Neural Anmentioning
confidence: 99%
“…PK was significantly elevated in the lateral preoptic and suprachiasmatic nuclei of the anterior hypothalamus and also in the medial mamillary nucleus and median eminence. No significant changes occurred in PFK activity.Since the phenomenon of androgen sterilization was initially described [Barraclough, 1961;Bradbury, 1941; P feiffer, 1936] 1973/1974; M en n in et al, 1974], and the hypothalamic locus thought to mediate the androgen effect [Barraclough, 1966; Barraclough and G o r sk i, 1961; G o r sk i, 1966;G orski and Barraclough, 1963; N adler, 1971, 1972, 1973 have been made. Changes in the overall metabolism [L ibertu n et al, 1969; M o g u ilevsky and R u b in stein , 1967; M ogu ilevski et al, 1969;Scacchi et al, 1973], specific enzyme steps [G a z ir i and Ladosky, 1973; H u n t er and…”
mentioning
confidence: 99%
“…Since both the pituitary gland and ovaries from adult female rats injected with androgen in early infancy can function normally when transplant ed into an untreated host (Harris, 1970), it is believed that the permanent effects of neonatal androgen lie within the central nervous system. From testosterone implants in the brain, Nadler (1972Nadler ( , 1973 and Hayashi and Gorski (1974) have shown that the androgen acts primarily on the hypothalamus within the preoptic and ventromedial-arcuate areas. Barraclough (1968) has suggested that the androgen may produce functional changes in the suprachiasmatic-preoptic areas of the hypothalamus, which are necessary for cyclic gonadotropin release prior to ovulation in the female rat.…”
mentioning
confidence: 99%